Directed energy deposition of AlSi10Mg: Single track nonscalability and bulk properties. (September 2020) - Kiani, Parnian; Dupuy, Alexander D.; Ma, Kaka; Schoenung, Julie M.
Abstract: Additive manufacturing of Al alloys presents an opportunity to produce complex parts that leverage their high specific strength. This paper aims to study the effect of processing parameters on the fabrication of single tracks and thin walls using AlSi10Mg powder in L-DED. A processing window was identified to enable continuous single track deposition with a regular shape. Deposition of thin walls and single tracks were used as a guideline to deposit blocks. Blocks were deposited using L-DED, and the physical, microstructural, and mechanical properties of the samples were investigated. Results demonstrated that the morphology of the thin walls were a better indicator of the morphology of the block samples than single tracks were, and care must be taken when transitioning from depositing single tracks to bulk (thin walls and blocks) samples. Results from mechanical testing show slight inhomogeneity as a function of height within the build for elongation and ultimate tensile strength. Microhardness and yield strength, however, were mostly uniform throughout the build. Overall, the results of this study demonstrate that L-DED is suitable for depositing AlSi10Mg and obtaining mechanical properties superior to those achieved through casting. Graphical abstract: Unlabelled Image Highlights: Laser directed energy deposition (L-DED) is used to deposit AlSi10Mg. Single tracks, thin walls, and block geometries were deposited. A processing window is defined for successful single track and thin wall deposition. Single track parameters have limited scalability to bulk geometries. Slight inhomogeneity in the mechanical properties is observed due to the microstructure.